2008
DOI: 10.1088/0022-3727/41/22/225102
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of SnO2nanoparticles embedded in Al2O3

Abstract: Tetragonal Sn nanoparticles of ∼15 nm diameter are produced in Al 2 O 3 by direct Sn implantation at room temperature. After thermal annealing at 1000 • C in oxygen, the implantation-induced amorphous region recrystallized and the Sn nanoparticles turned into SnO 2 nanoparticles with an average diameter of ∼30 nm as revealed by transmission electron microscopy. While no absorption and photoluminescence (PL) are observed from the metallic Sn nanoparticles, SnO 2 nanoparticles exhibit an absorption edge at ∼280 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…This emission is attributed to the electron transition by defect levels such as O vacancies, Sn interstitials, and so on in the band gap. Generally, O vacancies are known to be the most common defects and usually act as radiative centers in luminescence processes [17][18][19][20][21]. Hence, the origin of the green emission in the PL spectra can be assigned to the recombination of electrons in the singly occupied oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…This emission is attributed to the electron transition by defect levels such as O vacancies, Sn interstitials, and so on in the band gap. Generally, O vacancies are known to be the most common defects and usually act as radiative centers in luminescence processes [17][18][19][20][21]. Hence, the origin of the green emission in the PL spectra can be assigned to the recombination of electrons in the singly occupied oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…The current results are in agreement with the previous report by Gu et al [35] Earlier reports indicated that SnO 2 nanoparticles exhibited a dominant peak near 401 nm, [27] while other SnO 2 nanomaterials show peaks around 430 nm. [26,36] Wang et al thought that the appearance of the 401 nm peak was independent of the concentration of oxygen vacancies, but due to structural defects or luminescent centers, such as nanocrystals and defects in the SnO 2 nanoparticles. [37] Her et al reported that SnO 2 nanoblades exhibit a broad dominant emission peak near 445 nm, and thought that the blue luminescence from the as-synthesized SnO 2 nanoblades could be attributed to oxygen-related defects, high density of oxygen vacancies, and tin vacancies that were introduced during growth.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Sklad et al have found 1-3 nm single crystalline (body-center cubic) precipitates of iron in sapphire implanted with 1 Â 10 17 Fe/cm 2 (150 keV) at 300 K [1]. Tetragonal Sn nanoparticles of $15 nm diameter are produced in Al 2 O 3 by direct Sn implantation at room temperature [2]. Xiang et al implanted 64 keV Ni ions in a-Al 2 O 3 up to a fluence of 1 Â 10 17 cm À2 in room temperature.…”
Section: Introductionmentioning
confidence: 99%